Study of water discharge in the Ulee Lheue Port Channel, Indonesia. Issue 1 (January 2020) - Setiawan, I; Isbah, F; Muhammad, M; Yuni, S M; Purnawan, S; Akram, A; Ilhamsyah, Y
Abstract: Ulee Lheue serve as ferry ports in Banda Aceh, covering an area of ±8 ha. The information on water flow entering the port channel is needed to determine the quantity of water and facilitating transportation at the port. This study includes the measurement of water depth, channel width, current velocity, water discharge, and tides which was conducted every 3 hours at three different water depth. On Jumada I (Jumadil awal) 1-29, 1435 Hijra, the highest and lowest water depth of 6.06 and 3.82 meters occurred in the 23rd and 10th day at 09:00 and 16:00 local time, respectively. The highest and lowest velocity of 0.357 and 0.01 m/s occurred in the 15th and 18th day at 09:00 and 12:00 local time, respectively. The strongest and weakest discharges of 177.93 m 3 /s and 9.47 m 3 /s occurred in the 12th and 28th day at 09:00 local time, respectively. The results found a strong correlation between water discharge and current velocity. Thus water discharge and currents play an important role in the channel stability and in controlling sea transportation in terms of scheduling the departures and arrival of ships.